G9a regulates tumorigenicity and stemness through genome-wide DNA methylation reprogramming in non-small cell lung cancer - Pangeni, Rajendra P. (Clin Epigenetics, 2020)
BACKGROUND: Eukaryotic histone methyltransferases 2 (EHMT2 or G9A) has been regarded as a potential target for non-small cell lung cancer (NSCLC) therapy. This study investigated the regulatory roles of G9A in tumorigenesis and stemness in NSCLC. We isolated and enriched tumor-initiating cells (TIC) from surgically resected NSCLC tissues by FACS and sphere formation assays. We then knocked down G9A using shRNA and carried out genome-wide 850K methylation array and RNA sequencing analyses. We carried out in vivo tumorigenecity asssay using mice xenografts and examined G9A interactions with its novel target using chromatin Immunoprecipitation (ChIP). RESULTS: We identified 67 genes hypomethylated and 143 genes upregulated following G9A knockdown of which 43 genes were both hypomethylated and upregulated. We selected six genes (CDYL2, DPP4, SP5, FOXP1, STAMBPL1, and ROBO1) for validation. In addition, G9A expression was higher in TICs and targeting G9a by shRNA knockdown or by selective inhibitor UNC0642 significantly inhibited the expression of cancer stem cell markers and sphere forming capacity, in vitro proliferation, and in vivo growth. Further, transient overexpression of FOXP1, a protein may promote normal stem cell differentiation, in TICs resulted in downregulation of stem cell markers and sphere forming capacity and cell proliferation in vitro indicating that the genes we identified are directly regulated by G9A through aberrant DNA methylation and subsequent expression. Similarly, ChIP assay has shown that G9a interacts with its target genes through H3K9me2 and downregulation of H3K9me2 following G9a knockdown disrupts its interaction with its target genes. CONCLUSIONS: These data suggest that G9A is involved in lung cancer stemness through epigenetic mechanisms of maintaining DNA methylation of multiple lung cancer stem cell genes and their expression. Further, targeting G9A or its downstream genes could be a novel therapeutic approach in treating NSCLC patients.